Concept of Nafs in the Alquran - Yani, Lelti Saputri; Adila, Nesria; Sadriana, Fifi; Taufan, Muhammad (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2023)
Psychology is a science that studies human experiences, such as feelings, five senses, thoughts, and will. Islamic psychology studies convey problems regarding human psychology, inner intricacies, and ruhual solutions that refer to Islamic normative law. The Quran commentary on human physique includes insane, ins, nas, or some basyar, and sons of Adam or Adam's descendants. Meanwhile, mental or psychological studies are broader, starting from nafs, ar-ruh, al-qalb, and al-'aql. This research aims to explain the concept nafs or human qalb, ruh, al-qalb, 'aql, and its relationship in the Alquran. This research uses a qualitative method with a content analysis approach, all data is taken from various sources originating from psychology books, religious psychology books, the Alquran, theories, and expert opinions. All data that has been collected is then analyzed thematically, in other words, the themes that have been obtained are described comprehensively and in-depth. To make it more interesting, all themes from the results of this research will be discussed with the results of studies by previous researchers and qalb issues in the Alquran. This research gets results that concepts and relationships nafs (qalb) with ruh, qalb, and aql in the structure of human personality which becomes the ruhual substance in human formation. Nafs is an element formed from the entry of the qalb into the human body. Because it has elements of the hereafter and the worldly, then the qalb tends to do good and bad by using the aql. Therefore, man must guide his qalb with a clear qalb. The implications of this research are to provide reading material that helps readers understand it.